1994
DOI: 10.1038/bjc.1994.483
|View full text |Cite
|
Sign up to set email alerts
|

S-phase fraction and survival benefit from adjuvant chemotherapy or radiotherapy of breast cancer

Abstract: Summary Cancer chemotherapy interacts with cell proliferation, but data on the relationship between cancer cell replication and the effect of adjuvant chemotherapy are scarce. We have investigated the S-phase fractions of the primary tumour from premenopausal breast cancer patients who participated in a randomised trial comparing 12 cycles of polychemotherapy (CMF) with post-operative radiotherapy. DNA flow cytometry was performed on frozen tissues from 208 primary breast carcinomas, of which the S-phase fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Supporting this, our present and other results published previously (30) identify a direct association between high levels of CA and Ki-67, a cell proliferation marker. Proliferating cells are more sensitive to chemotherapeutical agents, and a positive correlation between proliferation rate and quality of prognosis after chemotherapy treatment has already been noted in other malignancies such as breast cancer, melanoma, and lymphoma (31)(32)(33). Moreover, in vitro experiments have shown that CA correlates with the sensitivity of human cancer cells to the cytotoxic effect of 5-fluorouracil (34), further supporting our observations.…”
Section: Discussionsupporting
confidence: 74%
“…Supporting this, our present and other results published previously (30) identify a direct association between high levels of CA and Ki-67, a cell proliferation marker. Proliferating cells are more sensitive to chemotherapeutical agents, and a positive correlation between proliferation rate and quality of prognosis after chemotherapy treatment has already been noted in other malignancies such as breast cancer, melanoma, and lymphoma (31)(32)(33). Moreover, in vitro experiments have shown that CA correlates with the sensitivity of human cancer cells to the cytotoxic effect of 5-fluorouracil (34), further supporting our observations.…”
Section: Discussionsupporting
confidence: 74%
“…Despite this, no correlation between cyclin A activity and response rate, TTP and OS calculated from the start of chemotherapy was found. A previous study from a randomised trial comparing adjuvant chemotherapy (cyclophosphamide, methotrexate and 5-fluorouracil) to radiotherapy in primary breast cancer showed that the benefit from chemotherapy was more pronounced among patients with tumours with a high S-phase fraction (Stal et al, 1994). Thus, the strong contrast between the adverse prognostic impact of a high proliferation rate from diagnosis of the disease, but not after start of aggressive chemotherapy, may indicate that chemotherapy has improved the course of the disease, especially in highly proliferating tumours.…”
Section: Discussionmentioning
confidence: 99%
“…A similar correlation between a high proliferation rate and improvement of prognosis by CT has previously been noted in other malignancies including breast cancer, melanoma and lymphoma. (Joensuu et al, 1994;Stål et al, 1994;Hahka-Kemppinen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%